Association of Social Determinants of Health with Time to Diagnosis and Treatment Outcomes in Idiopathic Subglottic Stenosis. (October 2021) - Lee, Jaclyn; Huang, Li-Ching; Berry, Lynn D.; Anderson, Catherine; Amin, Milan R.; Benninger, Michael S.; Blumin, Joel H.; Bock, Jonathan M.; Bryson, Paul C.; Castellanos, Paul F.; Chen, Sheau-Chiann; Clary, Matthew S.; et al.
Objectives: To examine whether social determinants of health (SDH) factors are associated with time to diagnosis, treatment selection, and time to recurrent surgical intervention in idiopathic subglottic stenosis (iSGS) patients. Methods: Adult patients with diagnosed iSGS were recruited prospectively (2015-2017) via clinical providers as part of the North American Airway Collaborative (NoAAC) and via an online iSGS support community on Facebook. Patient-specific SDH factors included highest educational attainment (self-reported), median household income (matched from home zip code via U.S. Census data), and number of close friends (self-reported) as a measure of social support. Main outcomes of interest were time to disease diagnosis (years from symptom onset), treatment selection (endoscopic dilation [ED] vs cricotracheal resection [CTR] vs endoscopic resection with adjuvant medical therapy [ERMT]), and time to recurrent surgical intervention (number of days from initial surgical procedure) as a surrogate for disease recurrence. Results: The total 810 participants were 98.5% female, 97.2% Caucasian, and had a median age of 50 years (IQR, 43-58). The cohort had a median household income of $62 307 (IQR, $50 345-$79 773), a median of 7 close friends (IQR, 4-10), and 64.7% of patients completed college or graduate school. Education, income, and number of friends were not associated with time to diagnosis via multivariable linear regression modeling. Univariable multinominal logistic regression demonstrated an association between education and income for selecting ED versus ERMT, but no associations were noted for CTR. No associations were noted for time to recurrent surgical procedure via Kaplan Meier modeling and Cox proportional hazards regression. Conclusions: Patient education, income, and social support were not associated with time to diagnosis or time to disease recurrence. This suggests additional patient, procedure, or disease-specific factors contribute to the observed variations in iSGS surgical outcomes.